Architectural Representation in Medieval Textual and Material Culture - Bailey, Hannah M.,Kinsella, Karl,Thomas, Daniel (Arc Humanities Press, 2023)
Exploring architectural remnants of the past–from castles and cathedrals to village churches–and the work of writers, illuminators, and craftspeople, this volume demonstrates the pervasive nature of architecture as a category of medieval thought.
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung; Electronic books; Architektur; Architekturbild; Architekturzeichnung; Literatur; Sachkultur; Mittelalter